Impact and Citation Trends of Surveys Endorsed by the EUPSA Network Office in Pediatric Surgery: A Bibliometric Analysis - Doktor, Fabian; Hall, Nigel J.; Mesas-Burgos, Carmen; Zani-Ruttenstock, Elke; Pederiva, Federica; Sukhotnik, Igor; Dingemann, Jens; Pio, Luca; Kakar, Mohit; Gorter, Ramon; Soyer, Tutku (European Journal of Pediatric Surgery, 2025)
The European Pediatric Surgeons' Association (EUPSA) Network Office regularly endorses surveys that address controversial topics in pediatric surgery. However, the scientific impact of these within the medical literature remains unclear. To address this gap, we conducted a bibliometric analysis of all published EUPSA-endorsed surveys.Surveys endorsed by the EUPSA Network Office were reviewed for topic, journal, participation, bibliometric indicators (total number of citations and citations per article and year), and citing countries. Simple linear regression was used to determine citation time trends.Between 2013 and 2024, at least one survey was published each year (R2 = 0.26; p = 0.1). Most commonly, surveys were published in the European Journal of Pediatric Surgery (n = 15), and the most common survey topics included general pediatric (n = 7), thoracic (n = 4), and colorectal (n = 3) surgery. The average number of participants per survey was 167 ± 53, with 75% (range: 54–89%) European responses. The most cited surveys addressed esophageal atresia, necrotizing enterocolitis, and Hirschsprung's Disease. The median number of citations per survey was 11 (range: 1–160), with a median of 6 citations per year (range: 0–26). The total number of citations from all EUPSA Network Office-endorsed surveys increased over time (R2 = 0.75; p = 0.0006), and the average citation per article and year was consistent (R2 = 0.09; p = 0.34). Citations originated from 63 countries, mostly from the United States (n = 75), Germany (n = 64), and China (n = 44).Despite inherent limitations of survey-based research, the growing bibliometric impact of EUPSA Network Office-endorsed surveys highlights their scientific merit as an important tool for exploring current pediatric surgical practices, which will inform future multi-institutional studies.
Keywords: survey; pediatric surgery; European; EUPSA; network